Book Review - Francesco Della Puppa & Giuliana Sanò (eds.), Stuck and Exploited. Refugees and Asylum Seekers in Italy Between Exclusion, Discrimination and Struggles; Venezia: Edizioni Ca’Foscari, 2021, 362 pp. - Alèxia Rué (Dve Domovini, 2022)
At a time when the guarantees that international protection seemed to offer are being constantly undermined across the Global North, Stuck and Exploited offers a comprehensive approach to the current processes of retrenchment of reception rights and the dismantlement of reception structures through an in-depth analysis of the Italian case. With a strong ethnographic lens, Della Puppa and Sanò’s edited volume compiles 16 contributions of academics, activists, and practitioners working in the field of asylum to examine the processes of exclusion and discrimination of asylum seekers in their passage through an asylum reception system marked by arbitrariness, neglect, and opacity. Divided into two parts, the first part of the volume examines the national developments and characteristics of the Italian asylum reception system in its insertion within wider tendencies of migration governance through reception in the Global North. However, it does not fail to deepen in the particularities of different Italian regions and municipalities, highlighting how the implementation of national and EU policy is interpreted and reinterpreted at the local level and how, within this context, the discretion of “street-level bureaucrats,” as described by Lipsky, and other intermediaries, as well as the actions of social movements or the civil society can become a tool for “debordering” or yet another strategy of further control over migrants’ lives.